Advertising to Children in Schools: The Case of ‘Book’ Clubs - Pettigrew, Simone; Davies, S. (Legal Service Bulletin Co-Operative Ltd., 2015)
Today's children develop in a world very different to that of previous generations. The 'commercialisation of childhood' has been well documented and refers to the ways in which marketers are successfully targeting children as consumer segments. This is a growing trend reflecting the considerable market worth of children's own disposable income and their ability to influence their parents' purchases.